B-Cell-Based and Soluble Biomarkers in Body Liquids for Predicting Acute/Chronic Graft-versus-Host Disease after Allogeneic Hematopoietic Stem Cell Transplantation - Juric, Mateja Kralj; Shevtsov, Maxim; Mozes, Petra; Ogonek, Justyna; Crossland, Rachel E.; Dickinson, Anne M.; Greinix, Hildegard T.; Holler, Ernst; Weissinger, Eva M.; Multhoff, Gabriele (Frontiers in Immunology, 2017)
Allogeneic haematopoeitic stem cell transplantation (allo-HSCT) is the main curative therapy for haematological malignancy such as leukaemias, lymphomas or multiple myelomas and some haematological disorders. In this therapy cure of haematological diseases relies on graft-versus-malignancy effects by allogenic immune cells. However, severe post-transplant treatment-associated complications such as acute (aGVHD) and chronic graft-versus-host disease (cGVHD) limit this approach. Most research into GvHD has concentrated on the aGVHD while the more complex and multifaceted chronic form has been largely poorly investigated. Chronic GvHD (cGvHD) is a multi-organ allo- and autoimmune disorder and is the major cause of non-relapse morbidity and mortality following allo-HSCT, occurring in about 50% of patients, or 13-15,000 patients per year worldwide. Therefore, there is a high medical need for an early prediction of these therapy associated toxicities. Biomarkers have gained importance over the last decade in diagnosis, prognosis and in prediction of pending diseases or side effects. Biomarkers can be cells, factors isolated from target tissues, or soluble factors which can be detected in body fluids. In this review we aim to summarize some of the recent developments of biomarkers in the field of allo-HSCT. We will focus on cell-based biomarkers (B-cell subsets) for cGVHD and soluble factors including microRNA which are excreted into serum/plasma and urine. We also discuss the potential role of cytosolic and extracellular 70kDa-heat shock proteins (HSP70) as potential biomarkers for aGVHD and their role in preclinical models. Blood-based proteomic biomarkers have been used as predictors of treatment responses in patients with aGVHD for many years. More recently, plasma derived microRNAs (miRNA) have been found to serve as a biomarker to diagnose aGVHD. Another development relates to urine-based biomarkers that are usually detected by capillary electrophoresis and mass spectrometry. These biomarkers have the potential to predict the development of severe aGVHD (grades III-IV), overall mortality and the pending development of cGVHD in patients post-transplant.